2014
DOI: 10.1158/1535-7163.mct-14-0451
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Simvastatin and Metformin Combination Chemotherapy for Osseous Metastatic Castration-Resistant Prostate Cancer

Abstract: Docetaxel (DTX) chemotherapy remains a standard-of-care for metastatic castration-resistant prostate cancer (CRPC). DTX modestly increases survival, yet results in frequent occurrence of side-effects and resistant disease. An alternate chemotherapy with greater efficacy and minimal side-effects is needed. Acquisition of metabolic aberrations promoting increased survival and metastasis in CRPC cells include constitutive activation of Akt, loss of adenosine monophosphate-activated protein kinase (AMPK) activity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 52 publications
5
51
0
Order By: Relevance
“…Additionally, AMPKα activity, as determined by change in p-Ser-79 ACC, p-Ser-HMG-CoAR, and p-Ser-792 Raptor staining, was diminished in metastatic subject specimens compared to specimens from patients in the non-metastatic group. These clinical observations confirmed our in vitro data, which had compared AMPKα phosphorylation status, protein expression, and activity amongst hormone-dependent and hormone-refractory, metastasis-derived cell lines [14]. Potential biases exist in this work due to the inter-relationship between high Gleason grade and metastasis and between castration-resistance and metastasis: biopsy specimens of those patients who progressed to metastasis were on average of higher Gleason score, and an association between p-Ser-486/491 AMPKα1/α2 staining and both progression to metastasis and higher Gleason score was established; additionally, all CRPC specimens were metastasis specimens.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, AMPKα activity, as determined by change in p-Ser-79 ACC, p-Ser-HMG-CoAR, and p-Ser-792 Raptor staining, was diminished in metastatic subject specimens compared to specimens from patients in the non-metastatic group. These clinical observations confirmed our in vitro data, which had compared AMPKα phosphorylation status, protein expression, and activity amongst hormone-dependent and hormone-refractory, metastasis-derived cell lines [14]. Potential biases exist in this work due to the inter-relationship between high Gleason grade and metastasis and between castration-resistance and metastasis: biopsy specimens of those patients who progressed to metastasis were on average of higher Gleason score, and an association between p-Ser-486/491 AMPKα1/α2 staining and both progression to metastasis and higher Gleason score was established; additionally, all CRPC specimens were metastasis specimens.…”
Section: Discussionsupporting
confidence: 86%
“…We have previously shown that AMPKα activity is significantly inhibited by Ser-486/491 phosphorylation in cell culture and in vivo models of metastatic and castration-resistant prostate cancer [14]. We hypothesize that these findings may translate to clinical specimens and that progression to metastasis and castration-resistance in prostate cancer will be associated with decreased AMPKα activity and increased Ser-486/491 AMPKα1/α2 phosphorylation.…”
Section: Introductionmentioning
confidence: 84%
“…38,39) The combination of metformin and simvastatin was found to decrease the levels of phospho-Akt and phospho-AMPKα1/α2. 40) The inhibitory effect and mechanisms of metformin in combination with atorvastatin have previously not been reported. In the present study, we found the potent effects of metformin in combination with atorvastatin on prostate cancer cells were associated with a strong inhibition of the activation of the transcription factor NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Recently, pre-clinical data indicated a combination of metformin and statin was better than either drug alone in inhibiting primary tumor growth, metastasis to bone, and biochemical failure; human data on the joint effects of statins and metformin on PCa mortality are limited. 10,11 Because the majority of metformin users also take statins 12,13 some of the favorable outcomes observed among metformin users might be derived from statins.…”
Section: Introductionmentioning
confidence: 99%